Peripapillary choroidal vascularity quantification and characterization in healthy individuals - Guduru, Abhilash; Rasheed, Mohammed Abdul; Goud, Abhilash; Vupparaboina, Kiran Kumar; Agrawal, Rupesh; Lupidi, Marco; Chhablani, Jay; Chhablani, Preeti Patil (Nepalese Journal of Ophthalmology, 2020)
Introduction: To characterize the peripapillary choroidal vasculature in healthy individuals using the choroidal vascular index (CVI), a previously established more robust tool of measurement of choroidal vascularity than choroidal thickness.Methods: The peripapillary choroid in healthy individuals was analyzed using optical coherence tomography. OCT B-scan were analyzed using automated binarization, a previously established technique. This separates the choroidal layer into the stromal and vascular areas. Choroidal vascular index (CVI), the vascular area/total area, was computed for each image over the macula and the peripapillary area of the optic disc. Regression analysis and generalized estimating equation (GEE) were used to analyze various demographics, and CVI in the macula and each quadrant of the optic disc.Results: Fifty eight eyes of 29 healthy individuals were included. Mean age was 42±17 years. Average CVI at the macula was 0.583. Average peripapillary CVI was 0.643 (nasal), 0.598 (temporal), 0.621 (superior) and 0.623 (inferior). Regression analysis of variables demonstrated there was no significant relationship between the demographic variables and macular CVI. However, the analysis demonstrated age and CVI of the peripapillary area were significantly correlated. Further stratification revealed significantly higher CVI in the optic disc in subjects over 45.Conclusion: Peripapillary CVI in all quadrants is higher than macular CVI in all age groups. CVI significantly increases after the age of 45 in the peripapillary area but not macular area. This suggests that stromal area decline is greater than the decline of the luminal area in the choroid at the peripapillary area as age increases.